2012
DOI: 10.1182/blood-2011-11-388926
|View full text |Cite
|
Sign up to set email alerts
|

Novel myeloma-associated antigens revealed in the context of syngeneic hematopoietic stem cell transplantation

Abstract: Targets of curative donor-derived graftversus-myeloma (GVM) responses after

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…We and others have demonstrated that GvL responses are initiated and sustained by the development of coordinated cellular and humoral immunity against tumor antigens and are not limited to a sole alloantigen response (12)(13)(14)(15). These studies have further suggested that individual patients have unique profiles of immunogenic tumor antigens, likely reflecting the heterogeneity of the genetic alterations found in tumor cells from different patients as well as the diversity of HLA (12)(13)(14)(15). Based on these principles, vaccination with autologous, irradiated leukemia cells is an attractive approach to expand leukemia-reactive T cells, since this cancer vaccine formulation reliably includes personal tumor antigens and can potentially elicit polyclonal CD4 + and CD8 + antitumor T cell responses (16).…”
Section: Introductionmentioning
confidence: 99%
“…We and others have demonstrated that GvL responses are initiated and sustained by the development of coordinated cellular and humoral immunity against tumor antigens and are not limited to a sole alloantigen response (12)(13)(14)(15). These studies have further suggested that individual patients have unique profiles of immunogenic tumor antigens, likely reflecting the heterogeneity of the genetic alterations found in tumor cells from different patients as well as the diversity of HLA (12)(13)(14)(15). Based on these principles, vaccination with autologous, irradiated leukemia cells is an attractive approach to expand leukemia-reactive T cells, since this cancer vaccine formulation reliably includes personal tumor antigens and can potentially elicit polyclonal CD4 + and CD8 + antitumor T cell responses (16).…”
Section: Introductionmentioning
confidence: 99%
“…Id protein is not the only myeloma-specific antigen that can be targeted by the immune system, a variety of tumorassociated antigens have been identified in myeloma cells. Among the most studied, there are NY-ESO-1 (cancer testis antigen) [66], RHAMM-R3 (receptor for hyaluronic acid-mediated motility) [36], WT1 and MUC1 (see Table 3) [69] and DKK1 (Dickkopf-1 a Wnt/Bcatenin signaling inhibitor protein) [68]. NY-ESO-1 specific CTLs generated from MM patients were shown to kill primary myeloma cells, and a clinical trial evaluating the efficacy of a vaccination strategy targeting NY-ESO-1 in association with GM-CSF is underway.…”
Section: Cpg7909mentioning
confidence: 99%
“…However, no clinical studies employing DKK1-derived peptides have been performed so far. Recently, in syngenic hematopoietic stem cell transplant setting in which donor immune responses should exclusively target unique tumor epitopes, 6 new myeloma-specific antigens were discovered, although their immunological and clinical value has not been assessed yet [69]. Kang et al have identified two novel HLA-A2 restricted antigens derived by HLA-DOB exclusively expressed in B lineage cells and in thymic medullary epithelium, which were naturally processed and presented on MM cells.…”
Section: Cpg7909mentioning
confidence: 99%
“…39 Another study has shown that T-cell and humoral immune responses to myeloma-specific Ags are more common after autologous and syngeneic transplant than in untreated myeloma patients. 40 No studies have associated the development of autologous/ syngeneic GVHD with protection from relapse. This may be due to the lack of subsequent chronic GVHD in patients who develop acute autologous GVHD, as acute GVHD alone after allo-HCT for plasma cell myeloma does not seem to be associated with protection from relapse.…”
Section: Autologous Transplantation As a Platform For Cellular Immunomentioning
confidence: 99%